Marketing management - Yusniza Kamarulzaman; Nor Khalidah Abu (Oxford revision series, 2012)
The Oxford Revision Series: Marketing Management summarizes the key concepts and practices of marketing which are essential to understanding this important subject. This revision book provides a succinct exposition of all the main topics in marketing, and is divided into four parts, understanding marketing management, analyzing marketing opportunities, developing and managing the marketing mix and managing current issues in marketing. Chapters covering services management, global marketing, e-marketing, social and ethical strategies have also been included